An Innovative Life Measuring Application using IOT Technology - Subba Rao, BV; Sirisha, J (International Journal of Computer Sciences and Engineering, 2025)
Breathe is the life source for any being. In our proposed model we take the concept of breathe to gauge the life span of a human being. LMA is an innovative tool which will predict the life span of a human being. This application will use the IoT technology to metric the inhale and exhale of person. Based on the counts of breathe in and breathe out, our system will generate a report which tells us life span of a person from time to time.